COMPARISON OF WARM AND COLD WATER COMPRESS ON PAIN RESPONSE IN IMMUNIZED INFANTS (DPT-HB-HIB COMBINATION IMMUNIZATION) AT SUGI WARAS OKI PUBLIC HEALTH CENTER - Rahmadayanti, Ade Marlisa; Mulia, Bramtama Sukma; Febriyanti, Rani (Stetoskop: The Journal Of Health Science, 2025)
Immunization in infants is divided into two types, namely active and passive. Active immunization is an antigen that is injected into the body to form antibodies that can last for years. While passive immunization is the use of antibodies to prevent or treat infections. As a result of this injection, it is the main source of pain and suffering that can cause anxiety and trauma. Anxiety and trauma caused by immunization pain must be minimized immediately because it can increase the potential for children to experience phobias of needles and medical procedures and can also cause non-compliance with health services in the future. This study aims to determine the comparison of warm and cold water compresses on pain responses in immunized infants (DPT-HB-HIB Combination Immunization) at the Sugi Waras Health Center, OKI. This study was conducted using a pre-experimental method with a quasi-experimental approach and a posttest only design research design. The sample in this study was 10 infants, with pain intensity measurements measured using the FLACC Scale. The results of the study with warm water compresses showed that 60% had moderate pain and 40% had mild pain, while with cold water compresses it was known that 80% had mild pain and 20% had moderate pain. The results of the Independent Samples Test analysis showed that there was no comparison of effectiveness between warm water compresses and cold water compresses, with p-values ​​of 0.272 and 0.275 respectively. So both warm and cold water compresses are equally effective in reducing the scale of pain response in immunized babies.